SMALL BUSINESS DEVELOPMENT: A COMPARISON OF PROGRAMS IN AMERICAN CITIES AND COUNTIES - Atkinson, Christopher (The journal of contemporary issues in business and government, 2011)
This article focuses on local government small business development programs in the United States and their evolution as policy institutions over time, and examines the basis for local government provision of such services. The article examines a variety of race-conscious (minority and women-owned programs) and race-neutral (small business) policy approaches in large counties and cities in the United States, and finds a range of approaches and eligibility standards. While there is diversity in approach, it is not evident that such variety yields optimal results in all cases. The article suggests a need for greater focus on the outcomes of such programs, given resources expended and the political context of the decisions that lead to their creation, to determine whether programs provide ample benefit for cost. This may result in identification of best practices in framing business development initiatives, greater clarity of purpose, and accountability/transparency, leading to more informed and reasonable expectations from the client small business community.